(untitled) (Proceedings OPTIMAL, 2025)
Post Sectio Caesarea (SC) mothers are advised to mobilize, Post Sectio Caesarea (SC) mobilization aims to accelerate wound healing, improve circulation, prevent venous stasis, support optimal respiratory function, improve digestive function, reduce post-surgical complications. The purpose of this study was to determine the relationship between early mobilization after Caesarean section and the acceleration of surgical wound healing in postpartum mothers This study design uses the Correlational Survey method. A population of 39 postpartum mothers with the Simple Random Sampling technique obtained 36 respondents. The research data was taken using observation and interviews. After being tabulated, the data was analyzed using the Chi Square Test with a significance level of p-value <α (0.05). The results of the study showed that most of them did Early Mobilization faster as many as 28 (77.8%), most of the respondents had a fast surgical wound healing process as many as 26 (72.2%). The results of the analysis obtained a p value of 0.015 <α = 0.05, meaning that there is a Relationship between Early Mobilization Post Sectio Caesarea (SC) and Acceleration of Surgical Wound Healing in Postpartum Mothers in the Turi Lamongan Health Center Work Area. It is expected that health workers will improve counseling and information about surgical wound care, and monitor wound healing and improving the quality of health services.